2018
DOI: 10.1111/acem.13664
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Validation of a Checklist to Predict Short‐term Death in Older Patients After Emergency Department Admission in Australia and Ireland

Abstract: Background Emergency departments (EDs) are pressured environment where patients with supportive and palliative care needs may not be identified. We aimed to test the predictive ability of the CriSTAL (Criteria for Screening and Triaging to Appropriate aLternative care) checklist to flag patients at risk of death within 3 months who may benefit from timely end‐of‐life discussions. Methods Prospective cohorts of >65‐year‐old patients admitted for at least one night via EDs in five Australian hospitals and one Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 20 publications
0
40
0
2
Order By: Relevance
“…Our score was derived from a cohort of alert ED attendees. Although the 1‐year mortality in both cohorts was considerably higher than that of the general population of the same age, the patients were probably far less sick than those in which the “surprise question” and CriSTAL score has been tested. It remains to be demonstrated if this simple prognostic score is more effective in identifying the need for supportive and palliative care than the “surprise question” or the CriSTAL score.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our score was derived from a cohort of alert ED attendees. Although the 1‐year mortality in both cohorts was considerably higher than that of the general population of the same age, the patients were probably far less sick than those in which the “surprise question” and CriSTAL score has been tested. It remains to be demonstrated if this simple prognostic score is more effective in identifying the need for supportive and palliative care than the “surprise question” or the CriSTAL score.…”
Section: Discussionmentioning
confidence: 82%
“…A modification of the CriSTAL prognostic model has recently been suggested for the assessment of frail older ED patients. 6 However, it is clearly not practical to use complex or inconvenient scores, [7][8][9] or those that require laboratory information, 10,11 or access to large amounts of administrative data 12,13 on every patient attending an ED. The question "Would you be surprised if this patient died within the next 6 to 12 months?"…”
Section: Importancementioning
confidence: 99%
“…All 14 included studies reported demographic information regarding older people at EOL in the ED. In 11 studies, most older people requiring EOL care in the ED were female, but three studies reported more males than females . Mean/median age ranged from 74 to 84 years .…”
Section: Resultsmentioning
confidence: 99%
“…ACEP Geriatric Sect: Question 1 for latest #SGEMHOP authors—[Cardona 2019] notes accuracy of ISAR to CriSTAL, but [Carpenter 2015] highlighted numerous #GeriED instruments to predict mortality yet none displayed LR+ > 10 or LR– < 0.10 (or came close). How does CriSTAL compare to all?…”
Section: Top Social Media Commentarymentioning
confidence: 99%
“…Basic demographic data alone are insufficient to predict individual patient risk . Therefore, the purpose of this study was to validate a personalized risk score—the Criteria for Screening and Triaging to Appropriate aLternative care (CriSTAL)—in older patients presenting to the ED …”
Section: Introductionmentioning
confidence: 99%